2012
DOI: 10.1111/j.1600-0714.2012.01126.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mast cells in periapical cysts, dentigerous cysts, and keratocystic odontogenic tumors

Abstract: Immunohistochemical staining detected higher number of mast cells than histochemistry. The higher number of mast cells observed in inflamed lesions could indicate the participation of these cells in the inflammatory response in odontogenic lesions. The prevalence of degranulated mast cells in the deep region suggests intense activity of these cells, possibly related to growth of cystic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 19 publications
2
30
0
Order By: Relevance
“…These studies showed that the frequency of mast cells was higher in areas near the implanted biomaterial, suggesting that the cells produced the inflammatory response induced by the studied materials. According to de Noronha Santos Netto et al 26 , a significantly greater number of mast cells was observed in lesions with inflammation based on an analysis of the frequency and distribution of mast cells in inflamed and non-inflamed cysts. These data indicate that mast cells participate in various acute and chronic inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that the frequency of mast cells was higher in areas near the implanted biomaterial, suggesting that the cells produced the inflammatory response induced by the studied materials. According to de Noronha Santos Netto et al 26 , a significantly greater number of mast cells was observed in lesions with inflammation based on an analysis of the frequency and distribution of mast cells in inflamed and non-inflamed cysts. These data indicate that mast cells participate in various acute and chronic inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Odontogenic cysts are derived from the epithelium of the dental apparatus and constitute more than 95% of the cysts of the jaws. The far most common odontogenic cysts are RCs, DCs, and OKCs.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that mast cells are not easily recognized by hematoxylin and eosin, and may be confused with a variety of other cells and immature granulocytes 4 , the authors of the present study chose to assess these cells through toluidine blue staining. Since toluidine blue is a cationic dye, it exhibits the capacity to selectively integrate with the glycosaminoglycan-protein complex (highly ionized) 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Santos Netto et al 4 analyzed mast cells using the toluidine blue technique and an immunohistochemical technique involving anti-tryptase antibody (clone G3) with 20 periapical cysts, 20 dentigerous cysts (14 inflamed and six non-inflamed) and 20 keratocystic odontogenic tumors. They noted that the mean number of mast cells found using the immunohistochemical technique was higher than when using histochemistry (P <0.0001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation